Effect of non-essential amino acids (proline and glutamic acid) and sugar polyol (sorbitol) on brood of honey bees - Noor-ul-Ane, Muhammad; Jung, Chuleui (Frontiers in Ecology and Evolution, 2022)
Dietary nutrients provide fuel for the growth and development of insects as well as chemicals for their tissue construction. Apis mellifera L., an important pollinator, collects nectar and pollens from different plants to get their nutritional needs. Honey bees use protein for growth and development and carbohydrates as energy sources. Pollens predominantly contain proline and glutamic acid (non-essential amino acids). This is the first study to evaluate the role of proline, glutamic acid and sorbitol on bee broods. The composition of the diet can optimize the in vitro rearing process. Therefore, we elaborated on the possible impact of these amino acids and sugar alcohol on bee broods. This study aimed to achieve this objective by rearing honey bee larvae under different concentrations of proline, glutamic acid, and sorbitol (1, 4 and 8%), which were supplemented into the standard larval diet. The supplementation of proline helped the quick development of larvae and pupae of honey bees, whereas developmental time only decreased in pupae in the case of glutamic acid. The duration of the total bee brood development was the shortest (20.1 and 20.6 days) on Pro8 and Glu4, respectively. Proline only increased larvae survival (93.8%), whereas glutamic acid did not increase the survival of any brood stage. Pupal and adult weights were also increased with proline and glutamic acid-supplemented diets. Sorbitol did not change the developmental period of the honey bee brood but increased larval survival (93.7%) only at the lowest concentration (Sor1). The small concentration of sorbitol can be used to increase the survival of the honey bee brood. However, a higher concentration (Sor8) of sorbitol reduced the body weight of both pupae and adults. This study predicted that rearing bee brood could be one of the factors for the selectivity of pollen with higher proline and glutamic acid during the foraging of bees.